Procedimentos para a formulação da estratégia competitiva de empresas - Barbosa, Luís César Ferreira Motta [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The object of this research is to formulate the competitive strategy of companies and its general objective is to present a study on the theory of competitive strategy to show how the models and techniques resulting from it could be used for the formulation of competitive strategy of companies. The formulation of organizational strategy has been a difficult problem to solve for companies and considerable part of this difficulty stems from the fact of not having a sufficiently standardized method for preparing such a strategy from well-defined steps. The models of Porter and RBV, although they are widely accepted both in academia or the corporate world, are considered by many authors as complementary theories because they help not much in the competitive strategy of companies and not propose nor show how it could come to the formulation of competitive strategy of companies based on their prospects. Thus, it has been applied CAC model in a medium-sized jewelry; a sufficiently standardized model that allowed the development of competitive strategy of companies from steps welldesigned and easy to understand, which contributed to the company's management, object of study. However, it presented two models, through steps based on the thoughts of Porter and RBV, trying to show how the constructs arising from these models could prove to be applied. The study of these models was performed by means of literature, in which the differences and similarities were analyzed, the advantages and disadvantages of the methods available in the literature, confronting the main thoughts of current on the theory of competitiveness

O objeto da presente pesquisa é a formulação da estratégia competitiva de empresas e seu objetivo geral é apresentar um estudo sobre a teoria da Estratégia Competitiva para mostrar como os modelos e técnicas decorrentes dela poderiam ser utilizadas para a formulação da estratégia competitiva de empresas. A formulação da estratégia organizacional tem sido um problema de difícil solução para as empresas e parte considerável dessa dificuldade advém do fato de não se dispor de um método suficientemente padronizado que permita elaborar tal estratégia a partir de passos bem delineados. Os modelos de Porter e da RBV, apesar de terem grande aceitação tanto no meio acadêmico quanto no meio empresarial, são considerados por muitos autores como teorias complementares, pois não auxiliam muito na formulação da estratégia competitiva empresarial e não propõem e nem mostram como poderia vir a ser a formulação da estratégia competitiva empresarial baseada em suas perspectivas. Assim, aplicou-se o modelo CAC em uma joalheria de médio porte; um modelo suficientemente padronizado que permitiu a formulação da estratégia competitiva empresarial a partir de passos bem delineados e de fácil compreensão, que contribuiu para a gestão da empresa, objeto de estudo. Contudo, apresentaram-se dois modelos, através de passos baseados nos pensamentos de Porter e da RBV, tentando mostrar como os constructos oriundos desses modelos poderiam vir a ser aplicados. O estudo desses modelos foi realizado por meio de pesquisa bibliográfica, na qual foram analisadas as diferenças e semelhanças, as vantagens e desvantagens dos métodos disponíveis na literatura, confrontando o pensamento das principias correntes sobre a teoria da competitividade
Procedures for the formulation of competitive strategy of companies
Keywords: Concorrência; Joalherias; Planejamento estrategico; Negócios; Administração de empresas; Competition